The Management of an Open Biopsy Tract Site Infection and Ulceration in the Setting of Osteosarcoma. (6th July 2022) - Bowen, Stephen; Lepkowsky, Eric; Khan, Fazel
Abstract : Biopsy site infection in the setting of osteosarcoma is a potentially devastating complication. We present the case of a 16-year-old adolescent girl with a distal femur osteosarcoma who developed an open biopsy site ulceration and infection after initiation of neoadjuvant chemotherapy. This was treated with careful local excision of the ulcerated biopsy site and systemic antibiotic therapy throughout the duration of her chemotherapy course. She subsequently underwent wide resection of the tumor en bloc with a generous ellipse around the biopsy scar and reconstruction with cemented knee megaprosthesis. No recurrence of either infection or malignancy was observed. This case represents the successful treatment of a biopsy site ulceration and infection in a patient with osteosarcoma and may merit adoption in future instances of this complication.